SEJARAH DESA TENGON SUKU DAYAK KUMBA KECAMATAN AIR BESAR KABUPATEN LANDAK TAHUN 1984–2020 - Diman; Muhammad Syaifulloh (MASA : Journal of History, 2026)
Tengon Village, located in Air Besar District, Landak Regency, is the only village in West Kalimantan that is homogeneously inhabited by the Dayak Kumba ethnic group (a sub-cluster of the Bidayuhic group). This research aims to describe the formation process of Tengon Village in 1984, the dynamics of the community's social-cultural-economic life, as well as the impacts of development up to 2020. This study employs historical methods (heuristics, source criticism, interpretation, and historiography), relying on primary sources in the form of in-depth interviews with community and customary leaders, as well as secondary sources such as village archives, monographs, and Dayakology literature. The research findings indicate that Tengon Village was formed through the regrouping of five traditional hamlets (Tengon Kulum, Pelaik, Upas, Kadik I, and Kadik II) in 1984, initiated by Temenggung Sanden and other prominent figures. The change in status from hamlet to definitive village (in 1998) brought significant impacts, including improvements in infrastructure, access to electricity and clean water, as well as economic development based on pepper, rubber, and wetland rice plantations. However, the community's education level remains low, and dependence on subsistence agriculture continues to pose a challenge. This study enriches the treasury of local Dayak history and provides policy recommendations for the regional government in preserving cultural identity and accelerating rural development. Keywords: Tengon Village, Dayak Kumba, Bidayuhic, village formation, social-economic change, West Kalimantan